FIELD EVALUATION OF FUNGICIDES FOR THE MANAGEMENT OF RICE BLAST CAUSED BY Magnaporthe oryzae - P. MADHUSUDHAN *, I. PARAMASIVA, U. VINEETHA and CH. SREELAKSHMI, (The Journal of Research ANGRAU, 2023)
Rice blast caused by Magnaporthe oryzae is the major threat to rice production worldwide. Prochloraz 23.5% + tricyclazole 20% SE, prochloraze 45% EC, tricyclazole 75% WP, azoxystrobin 18.2% w/w + difenconazole 11.4% SC, difenconazole 25% EC, hexaconazole 5% EC and propiconazole 25% EC were evaluated at different concentrations against the rice blast disease under field conditions during 2019-20 at Agricultural Research Station, Nellore. Results revealed that out of seven fungicides prochloraz 23.5 % + tricyclazole 20 % SE @ 2 ml/l was found effective with 64.78 % reduction of the disease and highest grain yield of 6026 kg ha-1 which was at par with prochloraze 45% EC @ 2ml/l with recorded 59.40 % reduction of the disease and 5512 kg ha-1 of grain yield of rice. Remaining test fungicides: tricyclazole 75% wp @ 0.6 g/l, azoxystrobin 18.2% w/w + difenconazole 11.4 % SC @ 1ml/l, difenconazole 25% EC @ 1 ml/l, hexaconazole 5% EC @ 2ml/l and propiconazole 25% EC@1 ml/l managed the disease with 52.35 %, 44.25, 23.89, 24.85 and 20.03% reduction, respectively.